Pembinaan Karakter Religius Peserta Didik Melalui Budaya Sekolah di SMAN 2 Ponorogo - Ngadhimah, Mambaul; Ramdhani, Abdurrahman Ali; Wachid, Abdul; Nafi’, Abdun; Wibowo, Abdi (IAIN Ponorogo, 2023)
School culture is a routine, programmed activity organized by the school. Religious character is one of the important characteristics that students must have to prevent moral degradation by increasing religious awareness, where state public schools tend to be synonymous with not providing many religious activities compared to schools with a religious standard such as madrasas or Islamic boarding schools. However, SMAN 2 Ponorogo can prove that school culture can have a good impact on efforts to develop students' religious character even though they do not provide as much religious learning as in madrasas or Islamic boarding schools. This research aims to identify school culture, the development of religious character through school culture and its impact on the development of students' religious character. The data collection techniques used were observation, interviews and documentation. The data analysis technique used consists of data reduction, data presentation and drawing conclusions. The results of this research show that the development of students' religious character at SMA Negeri 2 Ponorogo is carried out programmatically through school culture, namely: (1) Routine Friday activities; (2) Islamic religious literacy; (3) Khatmil Qur'an; (4) Social services and compensation for orphans; (5) Dhuhur prayer in congregation; (6) Friday prayers; (7) Ramadhan Islamic Boarding School. The existence of a school culture, especially in efforts to develop religious character, can provide development of divine values and human values, so that it can have a good impact on improving the religious character of students. This is proven by the finding that students have awareness and independence in applying religious values both from divine values and human values such as the practice of religious fiqh, independent dhuha prayers, congregational prayers, recitations of the Qur'an, spiritual improvement , emotional and social during the month of Ramadan, have a spirit of generosity and like to give alms which is a form of social concern where they can apply these things in their daily lives while studying at school, outside school, even after they graduate and become alumni of school.